2021
DOI: 10.1093/geronb/gbab012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Correlates of Loneliness and Psychological Distress During the Lockdown Situation due to COVID-19. Effects of Age and Self-Perceptions of Aging

Abstract: Objectives To longitudinally analyze the correlates of loneliness and psychological distress in people exposed to the coronavirus disease 2019 (COVID-19) lockdown, exploring the effects of age and self-perceptions of aging (SPA). Methods A longitudinal follow-up of 1,549 participants was carried out at four different time points during the lockdown in Spain. Questions about the risk of COVID-19, age, SPA, family and personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 27 publications
9
50
0
3
Order By: Relevance
“…In other words, adults confined during the quarantine in Spain who showed higher levels of distress also showed negative affect, perceived higher levels of pain, sleep problems, and suppression of their emotions during the assessed period. These results support recent work on distress due to COVID-19, with relationships found between distress, sleep disturbances, negative affect, sleep problems (Losada-Baltar et al, 2020), and levels of pain (Wang et al, 2020). However, to our knowledge, studies focused on COVID-19 have not explored the role of certain emotion regulation strategies, such as cognitive reappraisal or emotional suppression, in psychological reactions to a pandemic and to confinement.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In other words, adults confined during the quarantine in Spain who showed higher levels of distress also showed negative affect, perceived higher levels of pain, sleep problems, and suppression of their emotions during the assessed period. These results support recent work on distress due to COVID-19, with relationships found between distress, sleep disturbances, negative affect, sleep problems (Losada-Baltar et al, 2020), and levels of pain (Wang et al, 2020). However, to our knowledge, studies focused on COVID-19 have not explored the role of certain emotion regulation strategies, such as cognitive reappraisal or emotional suppression, in psychological reactions to a pandemic and to confinement.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, levels of distress were higher, and sleep quality was lower in people living alone. In the same direction, loneliness has been strongly related to depression anxiety, PTSD, and distress during the pandemic (González-Sanguino et al, 2020;Losada-Baltar et al, 2020;Mazza et al, 2020), and in general, low social support and thwarted belongingness have been broadly related to depression and suicide ideation (Joiner, 2006;Klonsky & May, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research during the pandemic indicated that although older adults may express more pronounced fear of COVID-19, possibly related with the mass media announcements about their higher risk for severe illness and increased COVID-19-related mortality, generalised anxiety symptoms may decrease with age [ 51 ]. In addition, older age was related with less depressive symptoms [ 52 ] and psychological distress [ 53 ]. Furthermore, there was no evidence that older old adults (71–80 years) show a poorer psychological wellbeing during the pandemic, compared with younger old adults [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older people are more likely to have experienced both individual traumatic events and collective traumas, such as war, dictatorship [ 38 ], financial crises and natural disasters [ 59 ]. As such, they may be able to consider the current pandemic in a broader context, relativising its impact and show higher resilience against the COVID-19-related adverse mental health outcomes using adaptive resources [ 42 , 53 , 60 , 61 ]. Furthermore, most studies were conducted during the acute phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%